Research on Architecture and Energy-Saving Mechanism of Reconfigurable Flexible Network - Wanwei Huang; Binqiang Wang; Zhiming Wang; Bo Yuan (Dianxin kexue)
With the development of network service and the expanding of network size, there are many problems of expandability and energy consumption in current network. A reconfigurable flexible network（RFN）architecture was proposed, which could carry the reconfiguration of service capability and green energy-saving, and the loose coupling layering model, networking architecture, and networking technology of RFN were given. By constructing or changing the mapping relationship between service capability and resource, the further evolution of upper layer service was supported flexibly. And green energy-saving could be achieved in network equipment manufacturing industry, network level and node level. Results show that, as a new architecture for future, RFN provides the ideas and methods for reconfigurable service and green network.